The Evolution Of The Cookhouse To The Kitchen - Sobouti, Hooman; Ghasemi, Ali (The Turkish Online Journal of Design Art and Communication, 2016)
Throughout history architecture has undergone significant changes including the interior space of houses; however, in this regard, the design of the kitchen space has had an outstanding progress. The cookhouse which in the pattern of the traditional houses was always situated in the yard or the basement, has constantly been regarded as a secondary space; but after some development it has been situated next to the guest room and the bedrooms thus leading to the modern life comfort. In this paper which is both descriptive and analytical, the evolution of the cookhouse to the kitchen during the last century is studied. Also the role of the technology in altering a secondary space (a cookhouse) to a main multi-purpose space (a kitchen) is investigated.
Keywords: cookhouse; kitchen; technology; evolution; the design of the traditional house